Efficacy of Platelet Rich Fibrin versus chitosan as a hemostatic agent following dental extraction in patients on antiplatelet therapy - Sourav Sarkar; N.T. Prashanth; E.S. Shobha; Vinod Rangan; G. Nikhila (Journal of Oral Biology and Craniofacial Research)
Objectives: The aim of this study is to compare the effectiveness of Platelet Rich Fibrin gel and Chitosan gel dressing in providing hemostasis in patients receiving Oral Antiplatelet Therapy and also to evaluate their surgical healing outcome following dental extractions. Methodology: A total of 60 patients under Oral Antiplatelet Therapy indicated for tooth extraction were included for treatment in the study without altering the oral antiplatelet regimens. Patients were allocated equally in two groups; Group A: where PRF gel was packed into the extraction socket, while Group B: Chitosan hydrogel was packed. Timing of hemostasis was noted for each patient of both the groups. Patients were examined for any pain/secondary bleeding/healing/soft tissue dehiscence/alveolar osteitis in the extraction site on first, third and seventh post-operative days. Results: All extraction sockets with Platelet-rich fibrin achieved hemostasis in 2.64 min and sockets with Chitosan hydrogel achieved hemostasis in 1.182 min (p < 0.001). Post-operative pain in Group A sites (3.2, 1.4, 0.37 on 1st, 3rd & 7th day respectively) was significantly lower than the control sites (3.4, 1.67, 0.53 on 1st, 3rd & 7th day respectively) p-value 0.001, 0.001 respectively. Conclusion: In this study, Chitosan hydrogel dressing thus proved to be a superior hemostatic agent compared to PRF gel, that significantly shortens the clotting time following dental extraction in patients under antiplatelet therapy. But, PRF gel has superior wound healing properties than Chitosan with less postoperative pain following minor oral surgical procedures under local anesthesia.